The Practicality of Electronic Biology-Based Student Worksheets (LKPD) Scientific Approach - Nurafni Darwis; Andi Asmawati Azis; Dian Dwi Putri Ulan Sari Patongai (Indonesian Journal of Biology Education, 2023)
Development of Electronic Student Worksheets Based on Scientific Approach Plantae Material for Class X SMA Negeri 1 Kalukku. The research aims to develop an electronic worksheet based on a scientific approach to material plantae that meets practical criteria. This type of research is Research and Development (R&D) with the ADDIE development model which consists of five stages, namely analysis, design, development, implementation, and evaluation. The research subjects were biology teachers and students of class X IPA 1, SMA Negeri 1 Kalukku. Data was collected using several instruments, namely electronic worksheet validation sheets, teacher and student response questionnaire validation sheets and teacher and student questionnaires. The results of the research show that the developed electronic worksheet product is practical. The practicality test results from the teacher's response were 91.46% (very practical) and students' responses were 85% (very practical). Based on the results of the study, it can be concluded that the electronic worksheet products based on the scientific approach developed are practical.